Islamic-Based Knowledge Management and Project-Based Learning for Enhancing Students’ Creative Thinking - Basri, Hasan; Rulia, Rulia; Hisniati, Sally Badriya; Kurniasih, Nia; Hambali, Adang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2025)
This study investigates how integrating Islamic educational values with knowledge management and Project-Based Learning (PjBL) can strengthen students’ creative thinking in the Industrial 4.0 era. Employing a Research and Development (R&D) approach based on Borg and Gall, the research used a quantitative method across five senior high schools in West Java with 316 student participants. Data were collected using validated questionnaires (Cronbach’s α = .944) and analyzed using descriptive statistics and ANOVA in SPSS 21. The results reveal that PjBL integrated with Islamic values—such as ihsan (excellence), amanah (responsibility), and istiqamah (steadfastness)—effectively improves students’ creative thinking skills. No significant differences were found among the schools, indicating consistent model effectiveness. This study emphasizes that combining Islamic values with modern pedagogical and knowledge management strategies prepares students for the challenges of the Industrial 4.0 era while nurturing moral and intellectual excellence.